Image Transmission Over Wireless Channel - Singh, Arwinder (2005)
In this project, we investigate the basic image processing technique, which are the fast Fourier transforms, discrete cosine transform and discrete wavelet transform. With the basic understanding the methodology of JPEG and JPEG 2000 compression is studied.